(untitled) (Hoboken, N.J., 2009)
GARP's Fundamentals of Energy Risk Management introduces investors to the basic components and some of the basic terminology used in the energy industry. It covers the commodity cycle, energy use and sources, and various risk types, various energy products and the markets where energy is traded. It also introduces certain risk management fundamentals and real option thinking. The book is GARP's required text used by risk professionals looking to obtain their Certificate in Energy Risk Management
Keywords: Energy industries,Power resources,Risk management,Các ngành công nghiệp năng lượng,Quản lý rủi ro,Nguồn tài nguyên năng lượng; Risk management,Quản lý rủi ro